Desarrollo de un plan de mantenimiento para la trituradora móvil 1012t de la empresa Dismet S.A.S., Bogotá (2019)
This work is a maintenance plan centered on increasing the availability and reliability of the 1012T mobile crusher in which you will find a general description of the equipment, its operational context, codification and classification of its systems and subsystems, from there on, the strategies of failure Mode Analysis and Effects (AMEF) and priority risk number (NPR) to hierarchy the priority of each of the components and establish a series of preventive activities which will be based on inspection, lubrication, adjustment and cleaning, these activities will be contemplated in the Route of Lubrication and Route of Maintenance. In order to generate adequate control and registration, a series of formats have been designed for the administration and management of information complemented by a Database developed in Microsoft Access. Finally, maintenance management is measured based on universal management indicators of maintenance.